Relationships Between Organizational Citizenships Behaviour, Work Environment, and Organizational Commitment of Profesional Nurses, Tertiary Hospitals, Health Region 4, Ministry of Public Health - Dadkaew, Kittiya; Prachusilpa, Gunyadar; Laorpuksin, Suwannee (Journal of health and health management, 2023)
This study is a descriptive study. The objectives were to 1) study the level of organizational commitment and 2) study the relationships between organizational citizenship behavior, work environment, and organizational commitment of professional nurses in Tertiary hospitals, Health Region 4, the Ministry of Public Health. Subjects were 320 professional nurses, selected by simple random sampling. The tool used was a questionnaire consisting of 4 parts: 1) general information; 2) organizational citizenships behavior questionnaire; 3) work environment questionnaire; and 4) organizational commitment questionnaire. Parts 2-4 were examined for validity by experts with CVT values = .94, .94, and .91, respectively, and Cronbach’s alpha coefficients = .95, .96, and .96, respectively. The data were analyzed by using percentage, mean, standard deviation, and Pearson’s product-moment correlation coefficient. The major findings were as follows: 1) organizational commitment of professional nurses in tertiary hospitals, Health Region 4, the Ministry of Public Health, were at the moderate level overall (r=3.47); 2) organizational citizenships behavior had a positive relationship at the moderate level with the organizational commitment of professional nurses in tertiary hospitals, Health Region 4, at the statistical significance level of .05 (r=.372). The work environment had a positive relationship at the moderate level with the organizational commitment of professional nurses in tertiary hospitals, Health Region 4, at the statistical significance level of .05 (r=.409).